2022
DOI: 10.1055/a-1840-9737
|View full text |Cite
|
Sign up to set email alerts
|

Change Resistance and Clinical Practice Strategies in Audiology

Abstract: Background: Audiology is experiencing pressure from market forces that may change the profession’s nature. Research suggests understanding resistance to change and organizational culture may provide insights that facilitate change. Purpose: This study was designed to examine audiologists’ resistance to change, organizational culture, and clinical practices related to hearing aid pricing and audiology assistants. Research Design: This study utilized a cross-sectional, non-experimental, survey design. Study Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 28 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…This is interesting in light of the fact that nearly half of HHPs reported that they will support patients with OTC hearing aids purchased elsewhere and a quarter reported that they will sell OTC hearing aids in their clinic or website. Many HHPs have been preparing for OTC hearing aids by moving from bundled pricing (i.e., which bundles together HHP services and the cost of the hearing aid) to unbundled pricing (which differentiates prices for services vs. hearing aids) [12]. Nevertheless, having a high level of concerns towards OTC hearing aids and service delivery models may impact how HHPs advise their pa-to believe that consumers will have problems to identify and address common problems and lead to greater confusion, and business owners are likely to believe that the consumers will give up on amplification.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is interesting in light of the fact that nearly half of HHPs reported that they will support patients with OTC hearing aids purchased elsewhere and a quarter reported that they will sell OTC hearing aids in their clinic or website. Many HHPs have been preparing for OTC hearing aids by moving from bundled pricing (i.e., which bundles together HHP services and the cost of the hearing aid) to unbundled pricing (which differentiates prices for services vs. hearing aids) [12]. Nevertheless, having a high level of concerns towards OTC hearing aids and service delivery models may impact how HHPs advise their pa-to believe that consumers will have problems to identify and address common problems and lead to greater confusion, and business owners are likely to believe that the consumers will give up on amplification.…”
Section: Discussionmentioning
confidence: 99%
“…light of the fact that nearly half of HHPs reported that they will sup-C hearing aids purchased elsewhere and a quarter reported that they g aids in their clinic or website. Many HHPs have been preparing for y moving from bundled pricing (i.e., which bundles together HHP of the hearing aid) to unbundled pricing (which differentiates prices ng aids) [12]. Nevertheless, having a high level of concerns towards d service delivery models may impact how HHPs advise their pahearing aid consultations and/or include OTC devices in their practher healthcare professionals may also have some role to play in fa- Warranties and return periods will be worse Disagree:  Consumers will give up on amplification dy examined views of HHPs regarding OTC hearing aids by asking ents relating to several potential areas of concern.…”
Section: Sub-group Of Hhps Based On Their Views Of Otc Hearing Aidsmentioning
confidence: 99%
See 2 more Smart Citations